THE FATE OF ABSTRACTS AT THE ABN. Issue 10 (9th September 2014) - Odunsi, Sola; Kobylecki, Christopher; Jones, Matthew
Abstract : Aim: The primary aim of this study was to determine the publication rates of abstracts presented at the Association of British Neurologists (ABN) Meeting. Our secondary aim was to consider what factors would make an abstract more likely to be published, following presentation. Method: We searched titles and authors of abstracts presented at ABN Scientific meetings (2007–2009) using the Pubmed database. The number of articles published, rate of publication and the average latency to publication were determined. Results: Between 2007–2009 there were five ABN meetings, at which a total of 627 abstracts were presented. 244 of these abstracts were published in peer-reviewed journals, giving a total publication rate of 38.9%. The mean latency to publication was 18.6±14.6 months. Platform presentations were more likely to be published than posters (Chi-square test, p=0.002). Abstracts were most likely to be published in Journal of Neurology, Neurosurgery and Psychiatry. Conclusion: To our knowledge this is the first study reporting publication rates of abstracts presented at the ABN, showing comparable rates to other speciality meetings in the UK. The publication rate of abstracts presented at a scientific speciality meeting in peer-reviewed journals may reflect the quality of the research presented at that meeting.